Imaging Neuroinflammation? A Perspective from MR Spectroscopy. (November 2014) - Zahr, Natalie M.; Mayer, Dirk; Rohlfing, Torsten; Sullivan, Edith V.; Pfefferbaum, Adolf
Abstract Neuroinflammatory mechanisms contribute to the brain pathology resulting from human immunodeficiency virus (HIV) infection. Magnetic resonance spectroscopy (MRS) has been touted as a suitable method for discriminating in vivo markers of neuroinflammation. The present MRS study was conducted in four groups: alcohol dependent (A, n = 37), HIV‐infected (H, n = 33), alcohol dependent + HIV infected (HA, n = 38) and healthy control (C, n = 62) individuals to determine whether metabolites would change in a pattern reflecting neuroinflammation. Significant four‐group comparisons were evident only for striatal choline‐containing compounds (Cho) and myo‐inositol (mI), which follow‐up analysis demonstrated were due to higher levels in HA compared with C individuals. To explore the potential relevance of elevated Cho and mI, correlations between blood markers, medication status and alcohol consumption were evaluated in H + HA subjects. Having an acquired immune deficiency syndrome (AIDS)‐defining event or hepatitis C was associated with higher Cho; lower Cho levels, however, were associated with low thiamine levels and with highly active antiretroviral HIV treatment (HAART). Higher levels of mI were related to greater lifetime alcohol consumed, whereas HAART was associated with lower mI levels. The current results suggest that competing mechanisms can influence in vivo Cho and mI levels, and that elevations in these metabolites cannot necessarily be interpreted as reflecting a single underlying mechanism, including neuroinflammation.